Radon exposure delays the development of skin lesions in a mouse model of psoriasis - Lerchl, Sylvie; Wiedemann, Julia; Maier, Andreas; Papenfuß, Franziska; Unger, Kristian; Brand, Anna; Clausen, Björn E.; Fournier, Claudia (Frontiers in Immunology, 2025)
IntroductionThe chronic inflammatory skin disease psoriasis vulgaris is characterized by itchy plaques, often accompanied by life-threatening comorbidities severely impairing the quality of life and cause high socioeconomic costs. Despite the known cancer risk, radon inhalation is used as a treatment for various chronic inflammatory diseases, including psoriasis. Knowledge about the underlying mechanism is scarce, largely due to the lack of suitable mouse models. MethodsHere, we used transgenic mice that spontaneously develop chronic psoriatic skin lesions inflicted by constitutive low-level IL-17A-production by CD11c+ cells (CD11c-IL-17Aind/ind mice). Mice underwent single or multiple radon exposures under therapy relevant conditions and observed until plaque formation or predefined time points. Blood and tissue were collected for immunohistological analysis and immune phenotyping. Comprehensive transcriptome profiling of non-lesional skin was performed 3 days and 2 weeks after multiple radon exposures. Results and discussionFollowing multiple radon exposures, plaque formation was significantly delayed in CD11c-IL-17Aind/ind mice, although IL-17A concentrations were not reduced. Cellular and molecular analyses indicated transient immunosuppressive effects after radon exposure and, on the cellular level, pDCs were significantly reduced in lymph nodes. Comprehensive transcriptome profiling of non-lesional skin showed a different gene expression profile after radon exposure. Notably, at an early time point after exposure, the Tbx21 gene, associated with psoriasis initiation, and at a late time point Tgfbr1were significantly downregulated, Furthermore, genes related to the suppression of inflammation and immune activation (Ccr6), for example Gata3 and others were upregulated. This points to immune modulation after radon exposure. In line with this, pathway enrichment analysis revealed immunosuppressive effects related to T cell regulation, similar to UV radiation-induced response. ConclusionThis study provides the first evidence of the efficacy of radon treatment, including the underlying mechanisms in a preclinical mouse model.